Konstruksi Persepsi Pasangan Hidup oleh Mahasiswa Melalui Konsumsi Konten TikTok: Sebuah Studi Kasus di Universitas Muhammadiyah Ponorogo - Usamah Al Mahdi; Muhammad Yassir; Hariatul Hafidzah Mahmad Khory (Cakrawala: Journal of Religious Studies and Global Society, 2025)
Marriage is a sacred institution in Islamic teachings that marks the beginning of a new life with the spouse of choice. In this context, choosing a life partner is an important decision that is influenced by various factors, including social media. This study aims to analyze the influence of TikTok content consumption on students' perception in choosing a life partner. This study uses a qualitative approach with a case study design carried out at the University of Muhammadiyah Ponorogo. Data were collected through in-depth interviews with seven purposively selected informants, then analyzed descriptive-analytically. The results of the study show that TikTok content related to lifestyle, romantic relationships, and beauty standards has a significant influence on shaping students' perceptions of the ideal partner criteria. These findings indicate that TikTok, as one of the dominant social media platforms among the younger generation, plays an active role in the social construction process related to partner selection. This research contributes to the understanding of social dynamics in the digital era, especially in the context of the influence of media on the values and preferences of students in higher education.